Photo-activated, solid-state introduction of luminescent oxygen defects into semiconducting single-walled carbon nanotubes - Wieland, Sonja; El Yumin, Abdurrahman Ali; Settele, Simon; Zaumseil, Jana (The journal of physical chemistry. C, Energy, materials, and catalysis, 2024)
Oxygen defects in semiconducting single-walled carbon nanotubes (SWCNTs) are localized disruptions in the carbon lattice caused by the formation of epoxy or ether groups, commonly through wet-chemical reactions. The associated modifications of the electronic structure can result in luminescent states with emission energies below those of pristine SWCNTs in the near-infrared range, which makes them promising candidates for applications in biosensing and as single-photon emitters. Here, we demonstrate the controlled introduction of luminescent oxygen defects into networks of monochiral (6,5) SWCNTs using a solid-state photocatalytic approach. UV irradiation of SWCNTs on the photoreactive surfaces of the transition metal oxides TiOx and ZnOx in the presence of trace amounts of water and oxygen results in the creation of reactive oxygen species that initiate radical reactions with the carbon lattice and the formation of oxygen defects. The created ether-d and epoxide-l defect configurations give rise to two distinct red-shifted emissive features. The chemical and dielectric properties of the photoactive oxides influence the final defect emission properties, with oxygen-functionalized SWCNTs on TiOx substrates being brighter than those on ZnOx or pristine SWCNTs on glass. The photoinduced functionalization of nanotubes is further employed to create lateral patterns of oxygen defects in (6,5) SWCNT networks with micrometer resolution and thus spatially controlled defect emission.